A Musical of Khlui - Pieng - Or Solo : A Case Study of Kru Jumniean Srithaiphan’s Kraw - Nai Song Chan - Manasompong, Worrapoj; Pikulsri, Chalermsak (Journal of Fine and Applied Arts Khon Kaen University, 2022)
Phleng Kraw - Nai Song Chan is a song with a kind of beat called “Song Mai”. This song is performed by conducting a melody with six sounds: Do, Re, Ti, Me, La and Fa. In this study, the author has given a specific example of Phleng Look - Yon using the first sound called “Do” to understand the solo of Khlui - Pieng - Or. A solo of Phleng Kraw - Nai requires specific technique which is different from the basic melody. A solo of Khlui - Pieng - Or using Phleng Kraw - Nai a case study Kru Jamniean Srithaiphan is performed with a solo melody. It is based on a melodic pattern of the basic melody to create the solo. The non - rhythmic style with specific playing techniques are used to create an aesthetic in a song. These techniques are “Prib” and “Sabad” (flicking) with the sounds. A solo of Khlui - Pieng - Or using Phleng Kraw - Nai a case study Kru Jamniean Srithaiphan is a melodic solo and requires advanced performing skill.